Durability is associated with higher resistance to fatigue in elite vs recreational cyclists - Demay, R.; Masson, L.; Kerhervé, H. A. (29th Annual Congress of the European College of Sport Science, 2-5 July 2024, Book of Abstracts, 2024)
INTRODUCTION: In road cycling, the ability to perform maximum intensity efforts after hours of racing, or durability, can make a difference between winning and losing [1]. Specifically, differences between World Class and Continental-level athletes are best observed in the fatigued state [2][3], yet the reasons behind these level-dependent variations remain unclear. The aim of this study was to clarify the effect of prolonged duration exercise with interspersed maximal efforts on performance and fatigability in recreationally-trained and elite cyclists. METHODS: Twelve recreational (maximal oxygen uptake (VO2max):61.9±7.3 mL/min/kg, Critical Power (CP):298±31W) and six elite-level cyclists (VO2max:75.8±5.4mL/min/kg, CP:378±62W) rode on a cycle ergometer for three hours in the moderate-intensity domain (90% VT1: 221±42 vs 180±22W) interspersed with three exhausting bouts destined to deplete W` (3min all-out test, 3AOT) at 0, 90 and 180 min elapsed. Power and heart rate (HR) were continuously monitored. Blood lactate ([La]), expired gases and ratings of perceived exertion (RPE, 6-20 Borg scale) were recorded every 30 min during moderate intensity bouts. Expired gases were measured during, and lactate concentration measured 30-s after each 3AOT. Knee extensor maximal voluntary contractions (MVC) were measured after warm-up, immediately after each 3AOT, and again 10 minutes post each 3AOT. RESULTS: Elite cyclists were characterised by higher CP, VO2max, peak power (721±96 vs 591±98 W) and VT1 (244 ±45 vs 199 ±29W) than recreational cyclists. During moderate intensity cycling, there were no significant group or time differences in VO2, [La], RPE and HR. There were also no group differences in CHO consumption (2.3±0.5 vs 2.2±0.4 g/min) despite the higher absolute intensity and energy cost (20±3 vs 17±2 kcal.min-1) in the elite group. There were significant alterations from 1st to 3rd 3AOT, in total work (elite: 75±9 vs 81±10 kJ ; recreational: 62±9 vs 59±10 kJ) and [La] (elite: 13.4±3.2 vs 8.0±2.9 mmol.L-1 ; recreational: 9.2±3.9 vs 7.6±2.9 mmol.L-1). However, W decreased significantly only in recreational cyclists (10.1±1.4 vs 12.4±9.1 kJ). There were no significant changes in CP or VO2peak during the three 3AOT for both groups. Knee extensor MVC decreased only in recreational group (122±29 vs 104±32 Nm) with no differences in relative voluntary activation in both groups. CONCLUSION: The main finding of this study was that recreational athletes displayed higher fatigability than elite cyclists over the duration of the prolonged exercise. In elite athletes, initial force was not different after despite higher total work, higher work performed during each 3AOT, and higher W` expended during each 3AOT. Elite cyclists also had similar CHO but higher FAT contribution to total energy expenditure at moderate intensity.